2023
DOI: 10.1038/s41378-023-00506-2
|View full text |Cite
|
Sign up to set email alerts
|

1ppm-detectable hydrogen gas sensors by using highly sensitive P+/N+ single-crystalline silicon thermopiles

Abstract: Hydrogen (H2) is currently of strategic importance in the pursuit of a decarbonized, environmentally benign, sustainable global energy system; however, the explosive nature of H2 requires leakage monitoring to ensure safe application in industry. Therefore, H2 gas sensors with a high sensitivity and fast response across a wide concentration range are crucial yet technically challenging. In this work, we demonstrate a new type of MEMS differential thermopile gas sensor for the highly sensitive, rapid detection … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…The sensing properties of various H 2 sensors are summarized in Table . ,,, While the response time of metal oxide semiconductor gas sensors is typically on the order of several seconds, they require heating to very high temperatures. , Some thermochemical H 2 gas sensors exhibit a typical response time of ∼20 s. Many thermal catalytic H 2 sensors also have typical response and recovery times exceeding 10 s. Compared to these previously reported H 2 sensors, even at the operating temperature of 50 °C, our device demonstrates superior H 2 gas-sensing kinetics. To the best of our knowledge, our thermocatalytic H 2 sensor represents the current state-of-the-art in optimized comprehensive sensing capabilities in terms of response and recovery time, sensitivity, and manufacturing technology.…”
Section: Resultsmentioning
confidence: 90%
“…The sensing properties of various H 2 sensors are summarized in Table . ,,, While the response time of metal oxide semiconductor gas sensors is typically on the order of several seconds, they require heating to very high temperatures. , Some thermochemical H 2 gas sensors exhibit a typical response time of ∼20 s. Many thermal catalytic H 2 sensors also have typical response and recovery times exceeding 10 s. Compared to these previously reported H 2 sensors, even at the operating temperature of 50 °C, our device demonstrates superior H 2 gas-sensing kinetics. To the best of our knowledge, our thermocatalytic H 2 sensor represents the current state-of-the-art in optimized comprehensive sensing capabilities in terms of response and recovery time, sensitivity, and manufacturing technology.…”
Section: Resultsmentioning
confidence: 90%
“…144 The robust selectivity was achieved by embedding the nanowires in a hydrophobic poly(methyl methacrylate) (PMMA) matrix, which likely contributes to the longer response times. 143 Other designs that exploit the thermoelectric effect are emerging due to advances in microfabrication 145,146 techniques that support the production of new intricate thermopiles 142,145,146 consisting of n ∼ 20−30 microthermocouples wired in series. Thermopiles improve the sensitivity to temperature changes by amplifying the associated electrical potential: 149,150 = V n T (19) Zhang et al 146 fabricated thermopiles made from singlecrystalline silicon with a Pt NP@Al 2 O 3 catalyst.…”
Section: ■ Catalytic Sensorsmentioning
confidence: 99%
“…It is worth noting that combinations of the technologies employed in the associated references may ultimately produce lower detection limits on par with those exhibited by the most sensitive MOS sensors. The lowest detection limits used a conventional catalyst and a sensitive thermopile 146 and it was separately shown that Pt nanoparticle catalysts 142 improve sensitivity and responsiveness while also preventing sensor degradation. It would be particularly interesting to understand how lower operating temperatures effect sensor sensitivity.…”
Section: ■ Catalytic Sensorsmentioning
confidence: 99%
See 2 more Smart Citations